New layered double hydroxides intercalated with substituted pyrroles. 2. 3-(Pyrrol-1-yl)-propanoate and 7-(pyrrol-1-yl)-heptanoate LDHs - Tronto, Jairo; Leroux, Fabrice; Dubois, Marc; Taviot-Gueho, Christine; Naal, Zeki; Klein, Stanlei Ivair [UNESP]; Valim, Joao Barros (Elsevier B.V., 2006)
We report the synthesis and characterization of organic-inorganic hybrid materials: Zn-2-Al-LDHs (layered double hydroxides) containing 3-(1H-pyrrol-1-yl)-propanoate and 7-(1H-pyrrol-l-yl)-heptanoate as the interlayer anions. The LDHs were synthesized by the co-precipitation method at constant pH followed by hydrothermal treatment for 72 h. The materials were characterized by PXRD, C-13 CP-MAS NMR, TGA, and ESR. The basal spacing found by PXRD technique is coincident with the formation of bilayers of the intercalated anions. The solid state C-13 NMR showed that the interlayered anions remain identical after intercalation. ESR data suggest that the monomers connect each other in a limited number of guests when a thermal treatment is applied. The inorganic LDH sheets delay the temperature of degradation of the monomers. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: nanostructures; polymers; X-ray diffraction; nuclear magnetic resonance (NMR); electron paramagnetic resonance (EPR)